mirror of
https://github.com/kalmarek/GroupRings.jl.git
synced 2024-11-19 06:30:27 +01:00
add tests for sum of squares
This commit is contained in:
parent
558cbc78d8
commit
10f3a97576
@ -209,4 +209,91 @@ using GroupRings
|
||||
end
|
||||
|
||||
end
|
||||
|
||||
@testset "SumOfSquares in group rings" begin
|
||||
∗ = star
|
||||
|
||||
G = FreeGroup(["g", "h", "k", "l"])
|
||||
S = G.(G.gens)
|
||||
S = [S; inv.(S)]
|
||||
|
||||
ID = G()
|
||||
RADIUS=3
|
||||
@time E_R, sizes = Groups.generate_balls(S, ID, radius=2*RADIUS);
|
||||
@test sizes == [9, 65, 457, 3201, 22409, 156865]
|
||||
E_rdict = GroupRings.reverse_dict(E_R)
|
||||
pm = GroupRings.create_pm(E_R, E_rdict, sizes[RADIUS]; twisted=true);
|
||||
RG = GroupRing(G, E_R, E_rdict, pm)
|
||||
|
||||
g = RG.basis[2]
|
||||
h = RG.basis[3]
|
||||
k = RG.basis[4]
|
||||
l = RG.basis[5]
|
||||
G = (1-RG(g))
|
||||
@test G^2 == 2 - RG(g) - ∗(RG(g))
|
||||
|
||||
G = (1-RG(g))
|
||||
H = (1-RG(h))
|
||||
K = (1-RG(k))
|
||||
L = (1-RG(l))
|
||||
GH = (1-RG(g*h))
|
||||
KL = (1-RG(k*l))
|
||||
|
||||
X = (2 - ∗(RG(g)) - RG(h))
|
||||
Y = (2 - ∗(RG(g*h)) - RG(k))
|
||||
|
||||
@test -(2 - RG(g*h) - ∗(RG(g*h))) + 2G^2 + 2H^2 == X^2
|
||||
@test (2 - RG(g*h) - ∗(RG(g*h))) == GH^2
|
||||
@test -(2 - RG(g*h*k) - ∗(RG(g*h*k))) + 2GH^2 + 2K^2 == Y^2
|
||||
@test -(2 - RG(g*h*k) - ∗(RG(g*h*k))) +
|
||||
2(GH^2 - 2G^2 - 2H^2) +
|
||||
4G^2 + 4H^2 + 2K^2 ==
|
||||
Y^2
|
||||
|
||||
@test GH^2 - 2G^2 - 2H^2 == - X^2
|
||||
@test -(2 - RG(g*h*k) - ∗(RG(g*h*k))) + 4G^2 + 4H^2 + 2K^2 == 2X^2 + Y^2
|
||||
|
||||
@test GH^2 == 2G^2 + 2H^2 - (2 - ∗(RG(g)) - RG(h))^2
|
||||
@test KL^2 == 2K^2 + 2L^2 - (2 - ∗(RG(k)) - RG(l))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) + 2*GH^2 + 2*KL^2 ==
|
||||
(2 - ∗(RG(g*h)) - RG(k*l))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2(2G^2 + 2H^2 - (2 - ∗(RG(g)) - RG(h))^2) +
|
||||
2(2K^2 + 2L^2 - (2 - ∗(RG(k)) - RG(l))^2) ==
|
||||
(2 - ∗(RG(g*h)) - RG(k*l))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2(2G^2 + 2H^2) +
|
||||
2(2K^2 + 2L^2) ==
|
||||
(2 - ∗(RG(g*h)) - RG(k*l))^2 +
|
||||
2(2 - ∗(RG(g)) - RG(h))^2 +
|
||||
2(2 - ∗(RG(k)) - RG(l))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2(2 - ∗(RG(g*h*k)) - RG(g*h*k)) + 2L^2 ==
|
||||
(2 - ∗(RG(g*h*k)) - RG(l))^2
|
||||
|
||||
@test 2 - ∗(RG(g*h*k)) - RG(g*h*k) ==
|
||||
2GH^2 + 2K^2 - (2 - ∗(RG(g*h)) - RG(k))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2(2GH^2 + 2K^2 - (2 - ∗(RG(g*h)) - RG(k))^2) + 2L^2 ==
|
||||
(2 - ∗(RG(g*h*k)) - RG(l))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2(2GH^2 + 2K^2) + 2L^2 ==
|
||||
(2 - ∗(RG(g*h*k)) - RG(l))^2 +
|
||||
2(2 - ∗(RG(g*h)) - RG(k))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
8G^2 + 8H^2 + 4K^2 + 2L^2 ==
|
||||
(2 - ∗(RG(g*h*k)) - RG(l))^2 +
|
||||
2(2 - ∗(RG(g*h)) - RG(k))^2 +
|
||||
4(2 - ∗(RG(g)) - RG(h))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2GH^2 + 2KL^2 == (2 - ∗(RG(g*h)) - RG(k*l))^2
|
||||
end
|
||||
end
|
||||
|
Loading…
Reference in New Issue
Block a user